Derivativos, alavancagem e a crise de 2008 - Pombal, Claudia Simone Azevedo (2009)
This work was to study the subject of subprime, in order to raise the relevant literature origin, evolution and possible contours to the financial crisis of the century. The general objective was to investigate the reasons for the occurrence of the phenomenon and its consequences. Through literature search were raised the main causes of the crisis, top trends and possible solutions. The conclusion was that to circumvent the consequences of the crisis is believed to be necessary to review international agreements to make arrangements more open and reformulate some of the institutions defining the market economies.